Sosialisasi Pneumonia dan Imunisasi PCV (Pneumococcal Conjugate Vaccine) pada Ibu anak Balita di Desa Uevolo Parigi Moutong Sulawesi Tengah: Pneumonia Socialization and PCV Immunization (Pneumococcal Conjugate Vaccine) to Mothers of Toddlers in Uevolo Parigi Moutong Village, Central Sulawesi - Nasrul Nasrul; Fahmi Hafid; Zainul; Lisnawati; Andi Fatmawati Syamsu; Fajrillah; Selvi Alfrida Mangundap; Niluh Nita Silfia; Sova Evie; Ismunandar; Azizah Saleh; Sigit Muhammad Nuzul; Baharuddin Condeng; Taqwin Taqwin (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Pneumonia is an infectious disease that causes the biggest death of children worldwide. More than 800,000 children under five die each year from pneumonia. There has been no socialization about pneumonia and PCV immunization for toddler mothers in Uevolo Parigi Moutong Village. Purpose: To socialize pneumonia and PCV immunization to increase the knowledge of mothers of toddlers in Euvolo Village, Siniu District, Parigi Moutong Regency. Method: Community service is carried out by providing outreach through health counseling with banners about pneumonia and PCV immunization. The implementation of the activity was carried out at the Posyandu in Uevolo Village, Parigi Moutong Regency, Central Sulawesi Province on September 21 2022. The target of the dedication was 12 mothers of toddlers. Evaluation in the form of pretest and posttest which is measured on the same day. Results: Community service activities begin with a pre test. The opening question found that all of the mothers had never heard of pneumonia and PCV immunization. In the posttest, there was an increase in the knowledge of toddler mothers with an average value of 83. Conclusion: Outreach through health counseling with banners increases the knowledge of mothers of toddlers about pneumonia and PCV immunization. It is recommended that village midwives put up banners for pneumonia and PCV immunization at posyandu and other health services in the village.